2011
DOI: 10.1007/s00467-011-2006-7
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil for steroid-dependent nephrotic syndrome: a phase II Bayesian trial

Abstract: Mycophenolate mofetil (MMF) has emerged as a new therapeutic option in steroid-dependent nephrotic syndrome (SDNS). We conducted a phase II Bayesian trial of MMF in children with SDNS. Phase II trials, usually single-arm studies, investigate the effect of new treatments. Standard Fleming's procedure relies on observed results (relapse rate during the trial), whereas Bayesian approach combines observed results with prior information (expected relapse rate according to prior studies and clinical experience). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…Mycophenolate mofetil is well tolerated compared with other immunosuppressive agents, and its efficacy as a first-line treatment for frequently-relapsing and steroid-dependent nephrotic syndrome has been suggested [103][104][105]. The guideline by the Children's Nephrotic Syndrome Consensus Conference (CNSCC) (US) and the KDIGO guideline describe a 1-year administration of mycophenolate mofetil as an option for immunosuppressive therapy in patients with frequentlyrelapsing and steroid-dependent nephrotic syndrome.…”
Section: Mycophenolate Mofetilmentioning
confidence: 98%
See 1 more Smart Citation
“…Mycophenolate mofetil is well tolerated compared with other immunosuppressive agents, and its efficacy as a first-line treatment for frequently-relapsing and steroid-dependent nephrotic syndrome has been suggested [103][104][105]. The guideline by the Children's Nephrotic Syndrome Consensus Conference (CNSCC) (US) and the KDIGO guideline describe a 1-year administration of mycophenolate mofetil as an option for immunosuppressive therapy in patients with frequentlyrelapsing and steroid-dependent nephrotic syndrome.…”
Section: Mycophenolate Mofetilmentioning
confidence: 98%
“…Reported side effects of mycophenolate mofetil include gastrointestinal symptoms (diarrhea, abdominal pain) [92-95, 97, 103, 105], myelosuppression (leukocytopenia, anemia, thrombocytopenia) [93,100,105], and infection (herpes, varicella) [93, 100, 104] but can generally be reversed with dose reduction.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…Several small studies with limited statistical power have shown that MMF has steroid-sparing effects and reduces relapse rates in patients with FR-SSNS, albeit with varying efficacy. [11][12][13][14][15][16][17][18] We studied efficacy and safety of MMF in patients with FR-SSNS in comparison with CsA in a prospective randomized multicenter open-label crossover trial.…”
mentioning
confidence: 99%
“…Although they have benefi cial effects, CsA has a signifi cant risk of nephrotoxicity along with cosmetic effects and CsA-dependency, while CYC may cause gonadotoxicity and malignancy (13). Recently, MMF has emerged as an immunosuppressive agent devoid of nephrotoxicity and gonadal toxicity, which is benefi cial in managing children with FRNS (3,4,9), SRNS (1,2,13,14), SDNS (5,7,12,15) and CsADNS (6,7). However, it has compromising side effects including GI disturbances, anemia, leukopenia, predisposition to infection and malignancies, which may lead to dose reduction or even medication withdrawal (2,5).…”
Section: Discussionmentioning
confidence: 99%